Henry Green and the limits of modernism - Hentea, Marius (Sussex Academic Press, 2014)
Although Henry Green has been recognized by James Wood, David Lodge and John Updike as one of the most innovative writers of his time, his significant achievement remains largely neglected. This book provides a theoretically sophisticated and historically nuanced reading of Greens novels and makes the case for Greens importance in reconsiderations of modernism, late modernism, and post-war realism.